Cognitive And Neuropsychological Assessments For Co-Occurring Opioid And Amphetamine-Type Stimulant (COATS) Dependent Patients - Hashim, Norhamizah (2016)
Several studies have shown that individuals with drug dependence have poorer cognitive functions in the domain of executive functions. Studies investigating cognitive impairments in people with poly-drug use are limited. This study is designed to evaluate the scope and the specific patterns of deficits in cognitive and neuropsychological functioning among opiate and ATS (Dual Drug Dependence (DDD)) abusing individuals enrolled in a medication-assisted treatment in Hospital Universiti Sains Malaysia (HUSM), Kelantan.